2005
DOI: 10.2169/internalmedicine.44.794
|View full text |Cite
|
Sign up to set email alerts
|

A Technique for the Measurement of Visceral Fat by Ultrasonography: Comparison of Measurements by Ultrasonography and Computed Tomography

Abstract: Objective This study aims to create a method of calculating intra-abdominal visceral fat volume by using ultrasound (US). The visceral fat volume measured by US was evaluated by comparison with the volume measured by computed tomography (CT).Methods Eighty-seven patients (52 males and 35 females) were enrolled in this study. Both US and CT were performed, and the visceral fat volume was measured. Both the distance and thickness of the parameters in US were measured as follows: 1) the distance between the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
2
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 18 publications
6
107
2
9
Order By: Relevance
“…[17] It has become a used method to evaluate the fat thickness and distribution, as besides being reliable it is cheaper and widespread than the computed tomography (CT) and magnetic resonance imaging (MRI) measurements and does not have harmful effects such as radiation. [29] In this study, USG measurements showed that the both walking exercise groups result in the decrease of VFT after the 12 weeks. The difference of WC was detected as an independent variable which predicts the decrease of VFT.…”
Section: Discussionsupporting
confidence: 49%
“…[17] It has become a used method to evaluate the fat thickness and distribution, as besides being reliable it is cheaper and widespread than the computed tomography (CT) and magnetic resonance imaging (MRI) measurements and does not have harmful effects such as radiation. [29] In this study, USG measurements showed that the both walking exercise groups result in the decrease of VFT after the 12 weeks. The difference of WC was detected as an independent variable which predicts the decrease of VFT.…”
Section: Discussionsupporting
confidence: 49%
“…Ultrasonography has proved to be a suitable noninvasive and reliable tool for quantifying abdominal fat and has been found to be as useful as CT in evaluating abdominal fat (10,12,(20)(21)(22)(23)(24). In studies evaluating visceral adipose tissue with ultrasonography, area or thickness was measured and measurements of both VFA and visceral fat thickness by US were demonstrated to be consistent with VFA by CT measurements (10,12,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Regional adiposity can be assessed by using anthropometric data and imaging techniques [11,12]. Among imaging techniques, Ultrasonographic assessment has attracted a considerable attention, as it combines safety, cost-effectiveness, accuracy [13] and with effectiveness, in the quantification of visceral fat, similar to that of computed tomography [14].…”
Section: Discussionmentioning
confidence: 99%